PENGARUH PENGENDALIAN INTERNAL, MORALITAS INDIVIDU, DAN KOMPETENSI APARATUR TERHADAP PENCEGAHAN FRAUD - Juliandika, Dimas; Fitri, Fauziah Aida; Fadhlia, Wida; Fitri, Meutia (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2025)
This study explores the effects of internal control, individual morality, and apparatus competence on fraud prevention in local governance. The research was conducted among administrators and village government workers in Kuta Alam District, involving a sample of 55 respondents selected through a purposive sampling strategy. Data were collected and distributed through surveys and analyzed using multiple linear regression with IBM SPSS Statistics 25. The results indicate that internal control, individual morality, and apparatus competence positively affect fraud prevention. Internal control is identified as a critical factor with a strong positive influence, demonstrating its essential role in reducing fraud risks. Apparatus competence also significantly contributes to fraud prevention, highlighting the need for skilled and capable personnel to ensure accountability. However, individual morality shows only a minimal influence, suggesting its limitations in mitigating fraud independently. Strengthening internal controls and improving personnel competence are crucial strategies for enhancing governance and preventing fraudulent practices.